Severity of Peri-ictal Respiratory Dysfunction With Epilepsy Duration and Patient Age at Epilepsy Onset - Kanth, Kiran; Park, Katherine; Seyal, Masud (Frontiers in Neurology, 2020)
Respiratory dysfunction preceding death is fundamental in sudden unexpected death in epilepsy (SUDEP) pathophysiology. Hypoxia occurs with one-third of seizures. In temporal lobe epilepsy, there is volume loss in brainstem regions involved in autonomic control and increasing neuropathological changes with duration of epilepsy suggesting increasingly impaired regulation of ventilation. In animal models, recurrent hypoxic episodes induce long-term facilitation (LTF) of ventilatory function, however, LTF is less robust in older animals. LTF of ventilation may, to some degree, ameliorate the deleterious effects of progressive brainstem atrophy. We investigated the possibility that the duration of epilepsy, or age at epilepsy onset, may impact the severity of seizure-associated respiratory dysfunction. Patients with focal epilepsy undergoing video-EEG telemetry in the epilepsy monitoring unit (EMU) were studied. We found a significant relationship between age at epilepsy onset and duration of peri-ictal oxygen desaturation for focal seizures not progressing to bilateral tonic-clonic seizures, with longer duration of peri-ictal oxygen desaturation in patients with epilepsy onset at an older age but no significant relationships between duration of epilepsy or age at EMU admission and ventilatory dysfunction. Our findings suggest an intriguing possibility that LTF of ventilation may be protective when epilepsy starts at a younger age.